Structure of calling and vocation across gender and age cohort - Eldridge, Brandy M., author; Dik, Bryan J., advisor; Byrne, Zinta S., committee member; Feller, Richard William, committee member; Swaim, Randall C., committee member (Colorado State University. Libraries, 2010)
The Calling and Vocation Questionnaire (CVQ) is a measure based on Dik and Duffy's (2009) theoretical conceptualization of calling, which includes three dimensions: (1) a transcendent summons, (2) deriving or expressing meaning or purpose through work, and (3) prosocial orientation in work. Additionally, this definition posits two overarching aspects of calling: presence and search. Research has established the CVQ as a reliable, valid psychological instrument for the purpose of measuring calling. The present study sought to evaluate the structure of the measurement model of the CVQ by conducting confirmatory multigroup analysis within the structural equation model paradigm using four groups of college students: women and men in the first year, and women and men in the last year of their undergraduate degree program. The purpose was to assess the utility of the CVQ as a psychological measure for college students in general; that is, if the measurement model operates similarly across groups, the CVQ can be employed with increased confidence with college students, regardless of their subgroup membership (e.g., year in school, gender). Participants were students recruited from an institution of higher education in the Western United States. Results indicated that the initially proposed measurement model of the CVQ did not provide a good fit to the data. The model was modified by assigning all prosocial orientation items related to search for calling to the presence of calling factor, resulting in good model fit for all groups. Multigroup analyses indicated the revised measurement model remained consistent across all four groups, with the exception of one factor loading. Additional analyses were conducted assessing differences in means scores between the four groups. Results indicated no significant differences in presence of or search for calling across age cohort. Significant gender differences were found, whereby women scored higher than men on both presence of and search for calling. These results were confounded, however, by unequal distribution of majors between women and men. Based on these results, it was concluded that the CVQ shows promise as a measure with utility across various groups of college students. Future directions for research and practice are also explored.
Department Head: Ernest L. Chavez.
Keywords: vocation; scale construction; gender; college students; career development; calling; Vocation; College students -- Attitudes; Vocational guidance; Gender-based analysis; Cohort analysis